Global management of a common, underrated surgical task during the COVID-19 pandemic: Gallstone disease - An international survery (2020)
Background: Since the Coronavirus disease-19(COVID-19) pandemic, the healthcare systems are reallocating their medical resources, with consequent narrowed access to elective surgery for benign conditions such as gallstone disease(GD). This survey represents an overview of the current policies regarding the surgical management of patients with GD during the COVID-19 pandemic. Methods: A Web-based survey was conducted among 36 Hepato-Prancreato-Biliary surgeons from 14 Countries. Through a 17-item questionnaire, participants were asked about the local management of patients with GD since the start of the COVID-19 pandemic. Results: The majority (n = 26,72.2%) of surgeons reported an alarming decrease in the cholecystectomy rate for GD since the start of the pandemic, regardless of the Country: 19(52.7%) didn't operate any GD, 7(19.4%) reduced their surgical activity by 50–75%, 10(27.8%) by 25–50%, 1(2.8%) maintained regular activity. Currently, only patients with GD complications are operated. Thirty-two (88.9%) participants expect these changes to last for at least 3 months. In 15(41.6%) Centers, patients are currently being screened for SARS-CoV-2 infection before cholecystectomy [in 10(27.8%) Centers only in the presence of suspected infection, in 5(13.9%) routinely]. The majority of surgeons (n = 29,80.6%) have adopted a laparoscopic approach as standard surgery, 5(13.9%) perform open cholecystectomy in patients with known/suspected SARS-CoV-2 infection, and 2(5.6%) in all patients. Conclusion: In the ongoing COVID-19 emergency, the surgical treatment of GD is postponed, resulting in a huge number of untreated patients who could develop severe morbidity. Updated guidelines and dedicated pathways for patients with benign disease awaiting elective surgery are mandatory to prevent further aggravation of the overloaded healthcare systems.